Mikrorestrukturyzacja euroregionu Nysa - Przybyła, Zbigniew (Microrestructuring of Euroregion Nysa, 2006)
The article presents historical process of structural changes in Euroregion Nysa. Special attention has been paid to the working groups of this Euroregion. In the author's judgment, proceeding formalization of organizational structure of this institution can be noticed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1099, s. 403-410